(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article talks about the role of language in the formation of human consciousness, its further development, and the transmission of cultural and material values of the national heritage from generation to generation. It is noted that learning the history of the language begins with mastering the origin of linguistic units, knowing the formation of linguistic means, increasing a person’s interest in language, broadening his understanding of language, and satisfying his requirements for language and speech. The significance in linguistics of investigating the reasons for the use of phraseological units that are actively used in clear, figurative, and accessible communication is emphasized. Therefore, the article analyzes the fact that certain phraseological units in the Kyrgyz language are related to the qualities of intelligence, knowledge and literacy in a person based on linguistic materials.